(untitled) (Research, Society and Development, 2021)
The present work aims to review the literature identifying the importance of chemical compounds used in the biomechanical preparation of the root canal system, comparing the compounds most used in clinical practice to carry out the operative stage of irrigation. A bibliographic survey was carried out in the databases of PubMed, Scielo, Lilacs, Science Direct and book queries in the physical library of a private college, including studies that addressed irrigation in the treatment of root canal systems, with a delimited period of specific time between 2013 to 2021, excluding those with no direct relation to the subject. Following the inclusion criteria, the available abstracts were read and 20 articles were identified, which were part of this study. Given the above, each irrigating substance studied has its advantages and disadvantages, with Sodium Hypochlorite (NaOCl) being the most used irrigant for demonstrating antimicrobial action and the ability to dissolve organic tissue, providing success in the treatment of SCR, however, in high concentrations may present cytotoxicity to pulp and periradicular tissues. Thus, the knowledge of professionals about these solutions in their use is of fundamental importance, in order to understand the results that will be achieved in the operative stage of irrigation.